Ternary Blended Binder for Production of a Novel Type of Lightweight Repair Mortar - Pavlíková, Milena; Zemanová, Lucie; Záleská, Martina; Pokorný, Jaroslav; Lojka, Michal; Jankovský, Ondřej; Pavlík, Zbyšek (Materials (Basel, Switzerland), 2019)
The goal of the paper was development and testing of a novel type of ternary blended binder based on lime hydrate, metakaolin, and biomass ash that was studied as a binding material for production of lightweight mortar for renovation purposes. The biomass ash used as one of binder components was coming from wood chips ash combustion in a biomass heating plant. The raw ash was mechanically activated by grinding. In mortar composition, wood chips ash and metakaolin were used as partial substitutes of lime hydrate. Silica sand of particle size fraction 0⁻2 mm was mixed from three normalized sand fractions. For the evaluation of the effect of biomass ash and metakaolin incorporation in mortar mix on material properties, reference lime mortar was tested as well. Among the basic physical characterization of biomass ash, metakaolin and lime hydrate, specific density, specific surface, and particle size distribution were assessed. Their chemical composition was measured by X-Ray fluorescence analysis (XRF), morphology was examined using scanning electron microscopy (SEM), elements mapping was performed using energy dispersive spectroscopy (EDS) analyser, and mineralogical composition was tested using X-Ray diffraction (XRD). For the developed mortars, set of structural, mechanical, hygric, and thermal properties was assessed. The mortars with ternary blended binder exhibited improved mechanical resistance, lower thermal conductivity, and increased water vapor permeability compared to the reference lime mortar. Based on good functional performance of the produced mortar, the tested biomass ash could potentially represent a novel sustainable alternative to other pozzolans commonly used in construction industry. Moreover, reuse of biomass ash in production of building materials is highly beneficial both from the environmental and economic reasons especially taking into account circular economy principles. The ternary blended binder examined in this paper can find use in both rendering and walling repair mortars meeting the requirements of culture heritage authorities and technical standards.
Keywords: ternary blended binder; biomass combustion; lightweight mortar; pozzolanic activity; functional properties